RISIKO OPERASIONAL BANK DAN PERMODELANNYA - Iwan Lesmana (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2017)
Managing bank’s operational risks becoming an important feature of sound risk management practice in modern financial markets. The most important types of operational risk involve breakdown in internal controls and corporate governance, which could lead to financial losses through fraud, error or failure to perform. Development of statistic has accelarated banks to create internal operational risk models in different ways. Although those models created in different ways, they surely use the pattern of risk management that is developed by Basel Committee on Banking Supervision. Basel Committee on Banking Supervision has proposed three increasingly sophisticated approaches of operational risk, i.e basic indicator approach, standardized approach and advanced measurement approach. Applying those approaches will help banks to eliminate the operational risk, that will lead them to a better intermediation process.